Pengaruh Komunikasi, Beban Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai - Yuliana Fransiska; Zulaspan Tupti (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2020)
The purpose of this study was to determine the effect of communication, workload and motivation on employee performance either partially or simultaneously at Dinas Kependudukan dan Pencatatan Sipil Labuhanbatu Utara. This study uses an associative approach, which is research conducted to determine the effect or relationship between the independent variable and the dependent variable. The population and sample in this study were all permanent employees at Dinas Kependudukan dan Pencatatan Sipil Labuhanbatu Utara, totaling 32 people. The data collection technique used in this study was a questionnaire. The data analysis technique used is multiple linear regression analysis. The results showed that partially communication has an influence on performance. Partially workload has an influence on performance. Partially motivation has no significant effect on performance, and simultaneously communication, workload and motivation have a significant effect on employee performance at Dinas Kependudukan dan Pencatatan Sipil Labuhanbatu Utara.